Intellectual capital efficiency and its determinants - Kweh Q.L.; Chan Y.C.; Ting I.W.K. (Universiti Sains Malaysia Press, 2023)
This study applies a two-stage approach to examine intellectual capital efficiency and its determinants. In the first stage, we evaluate the intellectual capital efficiency of 25 Malaysian software companies by using the data envelopment analysis (DEA) approach. Our findings show that the sample companies have to first improve their technical efficiency, and subsequently scale efficiency. We also provide some information on how much and in which types of intellectual capital an inefficient software company needs to improve. In the second stage, we run ordinary least squares and Tobit regression analyses to examine determinants of intellectual capital efficiency. Sales growth appears to have a significantly positive influence on intellectual capital efficiency. This study may provide some information for software managers to improve their efficiency in intellectual capital management. Penerbit Universiti Sains Malaysia, 2015.